Alkaline electrolyzed water composite diaphragm and preparation method thereof
By setting up an aminosilane nanofiber layer between the support layer and the transport layer of the alkaline electrolytic water composite separator, the problem of insufficient binding stability of the existing separator is solved, and higher stability and electrolytic efficiency are achieved.
Patent Information
- Application Number
- CN202411861131.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-04-04
AI Technical Summary
The binding stability of the existing alkaline hydrolytic composite diaphragm and the porous membrane is insufficient, resulting in the risk of shedding and gas mixing in the membrane in actual applications, affecting the electrolytic efficiency and energy consumption.
An alternately distributed support layer and transport layer structure is adopted, and an aminosilane nanofiber layer prepared by electrospinning is set up as a reinforcement layer to enhance the binding force between the transport layer and the support layer and improve the stability of the composite film.
By enhancing the bonding force between the layers, the stability and ionic conductivity of the composite film are improved, the possibility of falling off between layers is reduced, the electrolytic efficiency is improved, and energy consumption is reduced.
Smart Images

Figure CN119753754A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of battery diaphragms, and in particular relates to an alkaline water electrolysis composite diaphragm and a preparation method thereof. Background Art
[0002] Hydrogen energy is an important part of the national energy system of the future society. By 2025, the amount of hydrogen produced by renewable energy will reach 100,000 to 200,000 tons per year. The process of hydrogen production by water electrolysis is simple, fully automated, and has high hydrogen purity and is environmentally friendly. Alkaline water electrolyzer hydrogen production is the most mature water electrolysis hydrogen production technology so far, and is widely used in industry. It is simple to operate and highly efficient. The alkaline water electrolyzer is mainly composed of electrodes and diaphragms. The electrolyzer is divided into an anode chamber and a cathode chamber, which are separated by a diaphragm. The electrolyzer is filled with electrolyte and has good conductivity. 30% to 40% KOH or NaOH solutions are generally widely used. During the electrolysis process, the anode produces oxygen, the cathode produces hydrogen, and the diaphragm prevents the mixing of hydrogen and oxygen.
[0003] Among them, the diaphragm is an important part that causes the internal resistance and additional energy loss of the electrolyzer. The research and development of diaphragms with high hydroxide conductivity, high bubble point pressure, high durability and low gas permeability is of great significance for the electrolysis of alkaline aqueous solutions. In the process of hydrogen production by alkaline water electrolysis, the diaphragm blocks hydrogen and oxygen on the one hand, and allows hydroxide ions in the solution to pass through on the other hand, ensuring the continuous electrolysis process and reducing the diaphragm resistance as much as possible to reduce energy consumption.
[0004] The diaphragms in the prior art include the first generation diaphragms, the main component of which is asbestos. However, its swelling property reduces the overall tensile strength of the diaphragm, and it is easily damaged by the impact of electrolyte and gas, which affects the current density distribution, increases the diaphragm resistance, and increases the electrolysis energy consumption. In addition, due to the poor hydrophilicity of polyphenylene sulfide (PPS) diaphragms, the electrolyte cannot fully enter the diaphragm pores, resulting in the aggregation of tiny bubbles on the diaphragm surface, increasing the diaphragm resistance and energy consumption. Polysulfone (PSF) diaphragms also have the problem of poor hydrophilicity, which causes hydrogen and oxygen tiny bubbles to easily gather on the diaphragm surface, affecting the flow of electrolyte and reducing current efficiency. At present, the main structure of the third-generation composite membrane is a three-layer structure, including a porous base membrane filled with slurry and a surface coating of the same thickness. In order to conduct ions while isolating the anode and cathode gases, the coatings on both sides of the base membrane are also called transmission layers. The thickness of the composite membrane is relatively large, usually 220 to 500 microns; but as the coating thickness increases, the surface resistance increases, and the internal holes formed after phase conversion and substitution are difficult to control. The transmission layer is prone to large finger-like holes, which affects the strength of the diaphragm and increases the risk of gas mixing. In actual applications, alkaline water diaphragms also have the defect of a long response time, which reduces the conversion efficiency. At the same time, the large amount of zirconium oxide particles added has the risk of falling off, which is a common problem in the industry.
[0005] The prior art discloses a bipolar electrolyzer for alkaline water electrolysis, wherein the diaphragm is a non-woven fabric prepared by electrospinning of polypropylene, polysulfone, polyphenylene sulfide polymer, etc., and has a support layer and a porous membrane structure on both sides to improve the electrolysis efficiency. However, the degree of mutual adhesion of the composite membrane structure needs to be improved, and after the support layer and the porous membrane are prepared separately, the stability needs to be improved.
[0006] Therefore, developing an alkaline water electrolysis composite diaphragm with a more stable structure has important research significance and application value. Summary of the invention
[0007] In order to solve the problem in the prior art that the bonding stability between the alkaline water electrolysis composite diaphragm support and the porous membrane needs to be further improved, the primary purpose of the present invention is to provide an alkaline water electrolysis composite diaphragm with a more stable structure.
[0008] Another object of the present invention is to provide a method for preparing the alkaline water electrolysis composite membrane.
[0009] Another object of the present invention is to provide an alkaline water electrolysis electrolyzer, comprising the alkaline water electrolysis composite diaphragm.
[0010] Another object of the present invention is to provide an alkaline water electrolysis hydrogen production system, comprising the alkaline water electrolysis electrolyzer mentioned above.
[0011] In order to achieve the above-mentioned invention object, the present invention adopts the following technical scheme:
[0012] The invention protects an alkaline water electrolysis composite diaphragm, comprising an alternately distributed support layer and a transmission layer, wherein a reinforcement layer prepared by an electrostatic spinning method is arranged between the support layer and the transmission layer; the reinforcement layer is an aminosilane nanofiber layer.
[0013] The present invention provides a reinforcing layer composed of an aminosilane nanofiber layer between the support layer and the transmission layer. Due to the structure of aminosilane, it can form a covalent bond with the polyphenylene sulfide resin of the support layer and can also combine with the hydroxyl groups carried by the inorganic particles of the transmission layer, thereby enhancing the bonding force between the transmission layer and the support layer, improving the stability of the composite membrane, and reducing the possibility of shedding between layers. At the same time, the inventors also found that the aminosilane nanofiber layer as a single layer can avoid the problem of combining with the inorganic particles inside the transmission layer when it is directly added to the transmission layer, thereby affecting the ion conduction efficiency of the transmission layer.
[0014] Preferably, the support layer and / or the transport layer are prepared by an electrospinning method.
[0015] In the present invention, preferably, the thickness of the alkaline water electrolysis composite membrane is 220-500 μm.
[0016] Preferably, the transmission layer comprises polymer materials and inorganic particles.
[0017] Preferably, the polymer material is at least one of polysulfone polymer materials, polyvinylidene fluoride, polyvinyl chloride or polypropylene.
[0018] More preferably, the polysulfone polymer material is a mixture of one or more of polysulfone, polyethersulfone or polyphenylsulfone.
[0019] Most preferably, the polysulfone polymer material is polysulfone.
[0020] In the art, the role of inorganic particles is to make the diaphragm hydrophilic. There is no particular limitation on the inorganic particles. For example, at least one inorganic substance selected from the group consisting of oxides or hydroxides of zirconium, titanium, bismuth, cerium, and lanthanum; oxides of elements of Group IV of the periodic table; nitrides of elements of Group IV of the periodic table, and carbides of elements of Group IV of the periodic table can be cited. Among these, from the perspective of chemical stability, oxides of zirconium, titanium, bismuth, cerium, and lanthanum, and oxides of elements of Group IV of the periodic table are preferred, and zirconium oxide (ZrO2) and titanium oxide (TiO2) are more preferred. These inorganic particles can be used alone or in combination of two or more. The surface of the inorganic particles is polar.
[0021] In the present application, the size of the inorganic particles refers to the prior art, preferably, the inorganic particles have a primary particle size of 50-100 nm. The primary particle size refers to the average particle size of the inorganic particles that have not been agglomerated in the spinning solution, and the test thereof is carried out in accordance with the prior art.
[0022] Preferably, the inorganic particles have a secondary particle size of 150-300 nm. The secondary particle size refers to the average particle size of the secondary particles formed by the agglomeration of the inorganic particles in the spinning solution, and the test is carried out according to the prior art.
[0023] Specifically, the primary particle size and secondary particle size of the inorganic particles are tested using a dynamic light scattering instrument.
[0024] Preferably, the inorganic particles are at least one of zirconium oxide, cerium oxide, titanium oxide or lanthanum oxide.
[0025] More preferably, the inorganic particles are zirconium oxide.
[0026] Preferably, the support layer comprises polyphenylene sulfide.
[0027] Preferably, the support layer further comprises polypropylene material. More preferably, the support layer further comprises styrene copolymer or maleic anhydride.
[0028] Adding polypropylene to the mixture of polyphenylene sulfide can improve the fluidity and molding processability of polyphenylene sulfide in the molten state to adapt to the electrospinning process. Furthermore, styrene copolymer or maleic anhydride elastomer can be added to improve the compatibility of polypropylene material and polyphenylene sulfide, improve the toughness of the support layer, and make the mixture more suitable for the electrospinning process.
[0029] Preferably, in the support layer, the mass ratio of polyphenylene sulfide to polypropylene is 6:4 to 9:1.
[0030] Most preferably, in the support layer, the mass ratio of polyphenylene sulfide to polypropylene is 7:3.
[0031] Preferably, the aminosilane of the aminosilane layer is selected from at least one of (3-aminopropyl)trimethoxysilane, aminopropyltriethoxysilane and anilinomethyltrimethoxysilane.
[0032] Preferably, the thickness of each single layer of the reinforcing layer is 5-10 μm.
[0033] Preferably, the thickness of each single layer of the transmission layer is 20-80 μm.
[0034] Preferably, the thickness of each single layer of the support layer is 10-100 μm.
[0035] As a typical structure, the alkaline water electrolysis composite diaphragm of the present invention includes two support layers and three transmission layers, i.e., the structure of transmission layer / reinforcement layer / support layer / reinforcement layer / transmission layer / reinforcement layer / support layer / reinforcement layer / transmission layer.
[0036] Preferably, the resistance of the alkaline water electrolysis composite membrane is less than 0.2Ω·cm 2 , more preferably, less than or equal to 0.15Ω·cm 2 .
[0037] Preferably, the mechanical strength of the alkaline water electrolysis composite membrane is greater than 15 MPa, more preferably, greater than or equal to 20 MPa.
[0038] The preparation method of the alkaline water electrolysis composite diaphragm comprises the following steps:
[0039] S1. Preparing a transmission layer spinning solution;
[0040] S2. Preparing a reinforcing layer spinning solution;
[0041] S3. Preparing a supporting layer material;
[0042] S4. The transmission layer, the reinforcement layer and the support layer are prepared by an electrospinning method to obtain the alkaline water electrolysis composite membrane.
[0043] In addition, each layer of the alkaline water electrolysis composite membrane provided by the present invention is prepared by an electrospinning process, which can make the pores of the transmission layer more uniform and the distribution of inorganic particles more even, thereby further improving the wettability, stability and ionic conductivity of the composite membrane.
[0044] In the prior art, the preparation of composite diaphragms by electrospinning is a relatively mature technology, so the electrospinning process of the present application can be carried out with reference to the prior art.
[0045] Preferably, the reinforcing layer spinning solution is prepared by dissolving aminosilane in a solvent to form a spinning solution with a mass fraction of 5 to 15 wt%.
[0046] Preferably, the solvent may be at least one of dimethyl sulfoxide, methanol or isopropanol.
[0047] Preferably, the spinning solution of the transmission layer is prepared by dissolving the polysulfone polymer material in a solvent, and then adding inorganic particles. If necessary, a thickener may be added to facilitate uniform spinning.
[0048] The solvent is preferably at least one of N-ethylpyrrolidone, N-methylpyrrolidone or dimethylacetamide, and more preferably N-ethylpyrrolidone.
[0049] The viscosity enhancer is preferably at least one of polyvinyl pyrrolidone or polyethylene glycol, and more preferably polyvinyl pyrrolidone.
[0050] Generally, the mass concentration of the polysulfone polymer material in the transmission layer spinning solution is 10-30 wt%.
[0051] The supporting layer raw material can be preheated and transferred to the machine for spinning after reaching a molten state.
[0052] Preferably, during the electrospinning process of the transmission layer and the reinforcement layer, the voltage is controlled to be 10-15 kV.
[0053] Preferably, during the electrospinning process of the transmission layer and the reinforcement layer, the feed rate is 0.1 to 0.5 mm / min.
[0054] Preferably, during the electrospinning process of the transmission layer and the reinforcement layer, the rotation speed of the receiver is 70-150 rpm.
[0055] Preferably, during the electrospinning process of the support layer, the voltage is controlled to be 30-45 kV.
[0056] The present invention protects an alkaline water electrolysis electrolytic cell, wherein the diaphragm of the electrolytic cell is the alkaline water electrolysis composite diaphragm.
[0057] The present invention also protects an alkaline water electrolysis hydrogen production system, comprising the above-mentioned electrolytic cell.
[0058] Compared with the prior art, the present invention has the following beneficial effects:
[0059] The alkaline water electrolysis composite membrane provided by the present invention has a reinforcing layer prepared by an electrospinning method between a support layer and a transmission layer, wherein the reinforcing layer is an aminosilane nanofiber layer, thereby enhancing the bonding force between the transmission layer and the support layer, improving the stability of the composite membrane, and reducing the possibility of shedding between layers. The obtained alkaline water electrolysis composite membrane has high wettability, faster responsiveness and ionic conductivity. BRIEF DESCRIPTION OF THE DRAWINGS
[0060] Figure 1 : The surface of the alkaline water electrolysis composite membrane sample prepared in Example. DETAILED DESCRIPTION
[0061] The present invention is further described below in conjunction with examples. These examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples that do not specify specific conditions are usually carried out according to conventional conditions in the art or according to the conditions recommended by the manufacturer; the raw materials, reagents, etc. used, unless otherwise specified, are all raw materials and reagents that can be obtained from commercial channels such as conventional markets. Any non-substantial changes and substitutions made by those skilled in the art on the basis of the present invention belong to the scope of protection claimed by the present invention.
[0062] Zirconia powder was purchased from Jinghuang JH-101, with a primary particle size of 50-70 nm and a secondary particle size of 150-180 nm, which was measured in the spinning solution by a dynamic light scattering instrument.
[0063] In a specific embodiment, the receiver of the electrospinning device is a drum collector.
[0064] Example 1 Alkaline water electrolysis composite membrane
[0065] S1. Prepare the spinning solution of the transmission layer: dissolve 35g of polysulfone (PSF) in 80g of N-ethylpyrrolidone (NEP) to obtain a solution with a mass concentration of about 30wt%, and stir mechanically for 4h at a speed of 500rpm to ensure complete dissolution. Add 30g of zirconium oxide powder and 1g of polyvinylpyrrolidone (PVP K90) to the above solution, add PVP first, then add zirconium oxide powder, stir to make it a uniform spinning solution, stir in a closed manner for 4h at a speed of 1000rpm, and then degas for 20min at a speed of 2000rpm. After degassing, the spinning solution of the transmission layer is obtained.
[0066] S2. Preparation of reinforcing layer spinning solution: Add 5 g (3-aminopropyl) trimethoxysilane to dimethyl sulfoxide (DMSO), mechanically stir for 30 min at a speed of 500 rpm to obtain a reinforcing layer solution with a mass concentration of 15 wt%.
[0067] S3. Prepare the raw material of the support layer: Dry the raw material polyphenylene sulfide (PPS) in a vacuum drying oven at 100°C for 24 hours with a vacuum degree of -0.08MPa. Then crush the polypropylene (PP) in a grinder for 5 minutes and let it stand to cool. Secondly, mix the dried PPS and PP powder in a weight ratio of 7:3 for half an hour until they are uniform. Turn on the heating device and heat the charging barrel to 340°C. When the temperature is stable, the support layer mixed polymer is obtained.
[0068] S4. Preparation of composite membrane by electrospinning:
[0069] (1) Wrapping a fluorine-based release film around a collector, filling a syringe with a transmission layer spinning solution, and pumping the solution into the syringe needle at a voltage of 15 kV and a rate of 0.2 mm / min, the drum collector speed is 80 rpm, the spinning distance is adjusted to 8 cm, the machine temperature is adjusted to 80° C., and the humidity is adjusted to below 40%, to obtain a first transmission layer with a thickness of about 50 μm;
[0070] (2) replacing the syringe filled with the reinforcing layer spinning solution, and pumping the syringe needle at a voltage of 10 kV and a rate of 0.5 mm / min, the drum collector speed is 80 rpm, the spinning distance is adjusted to 8 cm, the machine temperature is adjusted to 80 ° C, and the humidity is 40%, to obtain the first reinforcing layer with a thickness of about 10 μm;
[0071] (3) Turn on the heating device and heat the loading barrel to 340°C. When the temperature is stable, add the support layer mixed polymer and put the plunger into the barrel. When the melt begins to drip, increase the voltage to 45kV and use a melt spinning head to spin to form the first support layer with a thickness of about 40μm;
[0072] (4) replacing the syringe filled with the reinforcing layer spinning solution, and pumping the syringe needle at a voltage of 10 kV and a rate of 0.5 mm / min, the drum collector speed is 80 rpm, the spinning distance is adjusted to 8 cm, the machine temperature is adjusted to 80 ° C, and the humidity is 40%, to obtain a second reinforcing layer with a thickness of about 10 μm;
[0073] (5) replacing the syringe filled with the transmission layer spinning solution, and pumping the syringe needle at a voltage of 15 kV and a rate of 0.2 mm / min, the drum collector speed is 80 rpm, the spinning distance is adjusted to 8 cm, the machine temperature is adjusted to 80 ° C, and the humidity is below 40%, to obtain a second transmission layer with a thickness of about 50 μm;
[0074] (6) replacing the syringe filled with the reinforcing layer spinning solution, and pumping the syringe needle at a voltage of 10 kV and a rate of 0.5 mm / min, the drum collector speed is 80 rpm, the spinning distance is adjusted to 8 cm, the machine temperature is adjusted to 80 ° C, and the humidity is 40%, to obtain a third reinforcing layer with a thickness of about 10 μm;
[0075] (7) the voltage is increased to 45 kV, and a melt spinning head is connected to a charging barrel for spinning to form a second support layer with a thickness of about 40 μm;
[0076] (8) replacing the syringe filled with the reinforcing layer spinning solution, and pumping the syringe needle at a voltage of 10 kV and a rate of 0.5 mm / min, the drum collector speed is 80 rpm, the spinning distance is adjusted to 8 cm, the machine temperature is adjusted to 80 ° C, and the humidity is 40%, to obtain a fourth reinforcing layer with a thickness of about 10 μm;
[0077] (9) Replace the syringe filled with the transmission layer spinning solution, and pump the syringe needle at a voltage of 15 kV and a rate of 0.2 mm / min. The speed of the drum collector is 80 rpm, the spinning distance is adjusted to 8 cm, the machine temperature is adjusted to 80 ° C, and the humidity is below 40% to obtain the third transmission layer with a thickness of about 50 μm. After the spinning is completed, it is washed with alcohol to finally obtain an alkaline-water composite membrane made by electrospinning with a thickness of about 270 μm.
[0078] Example 2 Alkaline water electrolysis composite membrane
[0079] S1. Prepare the spinning solution of the transmission layer: dissolve 35g of polysulfone (PSF) in 80g of N-ethylpyrrolidone (NEP) to obtain a solution with a concentration of about 30wt%, and stir mechanically for 4h at a speed of 500rpm to ensure complete dissolution. Add 25g of zirconium oxide powder and 1g of polyvinyl pyrrolidone (PVP K90) to the above solution, add PVP first, then add zirconium oxide powder, stir to make it a uniform spinning solution, stir in a closed manner for 4h at a speed of 1000rpm, and then degas for 20min at a speed of 2000rpm. After degassing, the spinning solution of the transmission layer is obtained.
[0080] S2. Preparation of reinforcing layer spinning solution: Add 3 g (3-aminopropyl) trimethoxysilane to dimethyl sulfoxide (DMSO), mechanically stir for 30 min at a speed of 500 rpm to obtain a reinforcing layer solution with a mass fraction of 5 wt%.
[0081] S3. Preparation of supporting layer raw materials: Preparation of supporting layer raw materials: Dry the raw material polyphenylene sulfide (PPS) in a vacuum drying oven at 100°C for 24 hours with a vacuum degree of -0.08MPa. Then crush the polypropylene (PP) in a grinder for 5 minutes and let it stand to cool. Secondly, mix the dried PPS and PP powder in a weight ratio of 7:3 for half an hour until uniform. Turn on the heating device and heat the charging barrel to 340°C. When the temperature is stable, the supporting layer mixed polymer is obtained.
[0082] S4. Preparation of composite membrane by electrospinning: The process, steps and thickness of each layer are exactly the same as those of S4. in Example 1. Finally, an alkaline-water composite membrane made by electrospinning is obtained with a thickness of about 270 μm.
[0083] Example 3 Alkaline water electrolysis composite membrane
[0084] The spinning solution of the transmission layer, the spinning solution of the reinforcement layer, and the raw materials of the support layer are all consistent with those in Example 1.
[0085] S4. Preparation of composite membrane by electrospinning: The process and steps are the same as those in Example 1, and the thickness of each layer is adjusted by adjusting the spinning time as follows:
[0086] (1) The first transmission layer has a thickness of about 80 μm;
[0087] (2) The first reinforcement layer has a thickness of about 10 μm;
[0088] (3) a first support mesh having a thickness of about 60 μm;
[0089] (4) The second reinforcement layer has a thickness of about 10 μm;
[0090] (5) Second transmission layer, thickness about 80 μm;
[0091] (6) The third reinforcement layer has a thickness of about 10 μm;
[0092] (7) a second support mesh having a thickness of about 60 μm;
[0093] (8) fourth reinforcement layer, thickness of about 10 μm;
[0094] (9) The third transmission layer has a thickness of about 80 μm. After spinning, the membrane is washed with alcohol to obtain an alkali-water composite membrane made by electrospinning with a thickness of about 400 μm.
[0095] Example 4 Alkaline water electrolysis composite membrane
[0096] S1. Prepare the spinning solution of the transmission layer: dissolve 35g of polysulfone (PSF) in 80g of N-ethylpyrrolidone (NEP) to obtain a solution with a concentration of about 30wt%, and stir mechanically for 4h at a speed of 500rpm to ensure complete dissolution. Add 30g of zirconium oxide powder and 1g of polyvinyl pyrrolidone (PVP K90) to the above solution, add PVP first, then add zirconium oxide powder, stir to make it a uniform spinning solution, stir in a closed manner for 4h at a speed of 1000rpm, and then degas for 20min at a speed of 2000rpm. After degassing, the spinning solution of the transmission layer is obtained.
[0097] S2. Preparation of reinforcing layer spinning solution: 5 g of aminopropyltriethoxysilane was added to methanol for dilution, and mechanical stirring was performed for 15 min at a rotation speed of 100 rpm to obtain a reinforcing layer solution with a mass concentration of 15 wt%.
[0098] S3. Preparation of supporting layer raw materials: Preparation of supporting layer raw materials: Dry the raw material polyphenylene sulfide (PPS) in a vacuum drying oven at 100°C for 24 hours with a vacuum degree of -0.08MPa. Then crush the polypropylene (PP) in a grinder for 5 minutes and let it stand to cool. Secondly, mix the dried PPS and PP powder in a weight ratio of 7:3 for half an hour until uniform. Turn on the heating device and heat the charging barrel to 340°C. When the temperature is stable, the supporting layer mixed polymer is obtained.
[0099] S4. Preparation of composite membrane by electrospinning: The process, steps and thickness of each layer are exactly the same as those of S4. in Example 1. Finally, an alkaline-water composite membrane made by electrospinning is obtained with a thickness of about 270 μm.
[0100] Example 5 Alkaline water electrolysis composite membrane
[0101] The spinning solution of the transmission layer, the spinning solution of the reinforcement layer, and the raw materials of the support layer are all consistent with those in Example 1.
[0102] S4. Preparation of composite membrane by electrospinning: The process and steps of each layer are the same as those in Example 1, except that the thickness of each layer is made thinner and the desired overall thickness is achieved by increasing the number of layers. Specifically, the thickness of each layer is adjusted by adjusting the spinning time as follows:
[0103] (1) The first transmission layer has a thickness of about 20 μm;
[0104] (2) The first reinforcement layer has a thickness of about 5 μm;
[0105] (3) a first support mesh having a thickness of about 10 μm;
[0106] (4) The second reinforcement layer has a thickness of about 5 μm;
[0107] (5) The second transmission layer has a thickness of about 20 μm;
[0108] (6) The third reinforcement layer has a thickness of about 5 μm;
[0109] (7) a second support mesh having a thickness of about 10 μm;
[0110] (8) fourth reinforcement layer, thickness about 5 μm;
[0111] (9) a third transmission layer, with a thickness of about 20 μm;
[0112] (10) a fifth reinforcement layer, with a thickness of about 5 μm;
[0113] (11) a third support mesh having a thickness of about 10 μm;
[0114] (12) a sixth reinforcement layer, having a thickness of about 5 μm;
[0115] (13) a fourth transmission layer, with a thickness of about 20 μm;
[0116] (14) seventh reinforcement layer, thickness about 5 μm;
[0117] (15) a fourth support mesh having a thickness of about 10 μm;
[0118] (16) an eighth reinforcement layer, with a thickness of about 5 μm;
[0119] (17) a fifth transmission layer, with a thickness of about 20 μm;
[0120] (18) ninth reinforcement layer, with a thickness of about 5 μm;
[0121] (19) a fifth support mesh having a thickness of about 10 μm;
[0122] (20) a tenth reinforcement layer, with a thickness of about 5 μm;
[0123] (21) The sixth transmission layer has a thickness of about 20 μm. After spinning, the membrane is washed with alcohol to obtain an alkali-water composite membrane made by electrospinning with a thickness of about 220 μm.
[0124] Example 6 Alkaline water electrolysis composite membrane
[0125] The components of the spinning solution of the transmission layer and the spinning solution of the reinforcement layer are consistent with those in Example 1, but the spinning solution of the transmission layer is used for blade coating.
[0126] Instead of using melt electrospinning to prepare the support layer, the traditional fine filaments were directly used to weave the PPS mesh with a mesh size of 100 meshes, a thickness of 100 μm, and a wire diameter of 56 μm.
[0127] S4. Preparation of reinforcing layer by electrospinning: the process and steps are the same as those in Example 1. The thickness of the reinforcing layer on both sides of the supporting layer is controlled by adjusting the spinning time, which is 10 μm. Subsequently, a transmission layer is applied on the reinforcing layer with a thickness of 75 μm using a scraper. After completion, the reinforcing layer is washed with alcohol to obtain an alkaline-water composite diaphragm with a thickness of about 270 μm.
[0128] Comparative Example 1 Alkaline Electrolyzed Water Composite Diaphragm
[0129] The preparation method of the transmission layer and the support layer is the same as that of Example 1, except that there is no reinforcement layer, and the structure of the composite membrane is the first transmission layer / first support layer / second transmission layer / second support layer / third transmission layer. The thickness of the first transmission layer, the second transmission layer and the third transmission layer is about 60 μm, and the thickness of the first support layer and the second support layer is about 50 μm. Finally, an alkali-water composite membrane made of electrospinning is obtained, and the thickness is about 280 μm.
[0130] Comparative Example 2 Alkaline Electrolyzed Water Composite Diaphragm
[0131] The raw materials of the support layer are consistent with those of Example 1, except that aminosilane is added to the spinning solution of the transmission layer;
[0132] S1. Prepare the spinning solution of the transmission layer: dissolve 35g of polysulfone (PSF) in 80g of N-ethylpyrrolidone (NEP) to obtain a solution with a concentration of about 30wt%, and stir mechanically for 4h at a speed of 500rpm to ensure complete dissolution. Add 5g (3-aminopropyl) trimethoxysilane, 30g of zirconium oxide powder and 1g of polyvinylpyrrolidone (PVP K90) to the above solution, add aminosilane and PVP first, then add zirconium oxide powder, stir to make it a uniform spinning solution, stir in a closed state for 4h at a speed of 1000rpm, and then degas for 20min at a speed of 2000rpm. After degassing, the spinning solution of the transmission layer is obtained.
[0133] Preparation of composite membrane by electrospinning: The preparation method of the transmission layer and the support layer is the same as that of Example 1, except that there is no reinforcement layer, and the structure of the composite membrane is first transmission layer / first support layer / second transmission layer / second support layer / third transmission layer. The thickness of the first transmission layer, the second transmission layer and the third transmission layer is about 60 μm each, and the thickness of the first support layer and the second support layer is about 50 μm each. Finally, an alkali-water composite membrane made by electrospinning is obtained, and the thickness is about 280 μm.
[0134] Performance Testing and Results
[0135] The performance test methods and standards of the alkaline water electrolysis composite membranes of the embodiments and comparative examples of the present invention are as follows:
[0136] (1) Ionic conductivity (mS / cm): According to SJ / T 10171-2016, a composite membrane of 2.5×2.5 cm (the test area is a circle with a diameter of 2 cm) (prepared in each embodiment and comparative example) was immersed in ethanol for 2 hours, ultrasonically vibrated for 5 minutes, immersed in 3M potassium hydroxide solvent for 24 hours, and then placed in a stainless steel test chamber. An impedance spectrum of the membrane was obtained using an electrochemical workstation, and the intersection of the high-frequency part of the spectrum line with the real axis was taken as the impedance value, which was converted into ionic conductivity.
[0137] (2) Tensile strength (MPa): According to SJ / T 10171-2016, at a constant temperature of 25°C, the composite diaphragm was cut into sample strips of 1×6 cm, placed in a test fixture and clamped vertically, stretched at a speed of 50 mm / min until it broke, and the tensile strength was read.
[0138] (3) Contact angle: According to GB / T 30693-2014, the instrument was calibrated with a ceramic calibration rod, and the surface tension of the distilled water sample was tested and analyzed. The test temperature was 25°C, the standard value was 71.97 mN / m, and the left and right averages of the test results were 71.69 mN / m, which met the test requirements. The test cloth samples were cut into long strips and fixed with a clamp, and then the contact angle values of each sample at multiple locations were tested, and the average value was taken for the 6 points.
[0139] (4) Current density (A / m 2 ): Active area 15cm 2 The LSCF single stack is used as the electrolyzer, and the self-made composite membrane is used to replace the diaphragm. With 30% KOH as the electrolyte, the volt-ampere curve of the diaphragm is tested at 80°C with a DC power supply, a cell voltage of 1.5-2.0V, and a step size of 0.05V, and the current density of the system running stably at 1.8V is calculated. 1.8V current density (stable for 15 minutes): it reaches stability 15 minutes after the cell is put on, and can reach a stable current density quickly, shortening the activation time required for the diaphragm, that is, it has faster responsiveness; 1.8V current density (continuous 50h): the current density after continuous electrolysis for 50h is intended to reflect the overall stability of the diaphragm, whether there are defects such as mechanical shedding or chemical corrosion in the alkaline cell working environment.
[0140] The performance test results of the alkaline water electrolysis composite membranes in the embodiments and comparative examples according to the above-mentioned method are shown in Table 1.
[0141] Table 1 Performance test results of various embodiments and comparative examples
[0142]
[0143]
[0144] It can be seen from Table 1 that the alkaline water electrolysis composite diaphragms prepared in Examples 1 to 6 of the present invention all have stable structure, fast responsiveness, good wettability and ionic conductivity, among which Example 1 has the best comprehensive performance.
[0145] In Comparative Example 1, no reinforcement layer is set. When the thickness difference is small, the ionic conductivity decreases, the tensile strength decreases, the responsiveness is poor, and the overall stability of the diaphragm is poor. In Comparative Example 2, the main component of the reinforcement layer, aminosilane, is directly added to the transmission layer, and no reinforcement layer is set. The bonding of the composite diaphragm is not good enough. The performance has declined after 50 hours, and the current density is small, indicating that the electrical properties of the diaphragm are poor, and the tensile strength is also much smaller than that of the embodiment, proving the necessary role of the reinforcement layer.
[0146] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. An alkaline water electrolysis composite diaphragm, characterized in that: The invention comprises a supporting layer and a transmission layer which are alternately distributed, and a reinforcing layer prepared by an electrostatic spinning method is arranged between the supporting layer and the transmission layer; the reinforcing layer is an aminosilane nanofiber layer.
2. The alkaline water electrolysis composite diaphragm according to claim 1, characterized in that: The thickness of the alkaline water electrolysis composite diaphragm is 220-500 μm.
3. The alkaline water electrolysis composite diaphragm according to claim 1, characterized in that: The transmission layer includes polymer materials and inorganic particles.
4. The alkaline water electrolysis composite diaphragm according to claim 1, characterized in that: The support layer includes polyphenylene sulfide.
5. The alkaline water electrolysis composite diaphragm according to claim 1, characterized in that: The aminosilane of the aminosilane layer is selected from at least one of (3-aminopropyl)trimethoxysilane, aminopropyltriethoxysilane and anilinomethyltrimethoxysilane.
6. The alkaline water electrolysis composite diaphragm according to claim 1, characterized in that: The thickness of each single layer of the reinforcing layer is 5 to 10 μm.
7. The method for preparing the alkaline water electrolysis composite diaphragm according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1. Preparing a transmission layer spinning solution; S2. Preparing a reinforcing layer spinning solution; S3. Preparing a supporting layer material; S4. The transmission layer, the reinforcement layer and the support layer are prepared by an electrospinning method to obtain the alkaline water electrolysis composite membrane.
8. The preparation method according to claim 7, characterized in that: The reinforcing layer spinning solution is prepared by dissolving aminosilane in a solvent to form a spinning solution with a mass fraction of 5 to 15 wt%.
9. An alkaline water electrolysis cell, characterized in that: The diaphragm of the electrolytic cell is the alkaline water electrolysis composite diaphragm according to any one of claims 1 to 6.
10. An alkaline water electrolysis hydrogen production system, characterized in that: Comprising the electrolytic cell as claimed in claim 9.
Citation Information
Cited By
Composite diaphragm, preparation method of composite diaphragm, alkaline electrolytic cell and application of alkaline electrolytic cell
CN121204735A